Effects of Flow Patterns and Hemodynamic Force on Vascular Endothelium in the Temporary Arteriovenous Shunt Loop in Rabbits - Tanaka, Yoshio; Koghure, Tetsukuni; Ueno, Masaki; Sugiyama, Hitoshi; Hamamoto, Yhusuke; Tamai, Motoki; Taguchi, Noriyuki; Sakamoto, Haruhiko (Journal of Reconstructive Microsurgery, 2013)
The purpose of this study was to investigate whether there is a risk of thrombosis in the temporary arteriovenous shunt loop (TAVSL). The authors established a TAVSL model in the rabbit. Experimental groups were divided into non–heparin treated and heparin treated. The maximum blood flow volume, blood viscosity, and radius of curvature were measured, and the Reynolds number and the sheer stress were calculated. Computational fluid dynamics (CFD) was used to predict the flow pattern in the TAVSL, and these predicted data were compared with histological results. Early occlusion was noted in 70% (7/10) of the non–heparin-treated group and 22% (2/9) of the heparin-treated group. CFD analysis predicted a high shear stress at the arterial anastomosis region and the outer luminal surface of the curved section. The intimal structure at the luminal surface of the curved section was extensively lost histologically. In the patent group, severe stenosis of the lumen was noted at the apex of the loop due to an organized thrombus. Thus, thrombosis is likely to occur in the TAVSL due to endothelium injury caused by high shear stress, and this results in the formation of white thrombi at an early stage and an organized thrombus at a late stage.
Keywords: areteriovenous shunt loop; endothelial injury; hemodynamic force